Implementasi Landasan Pengembangan Kurikulum pada K13 dan Kurikulum Merdeka - Ap, A. Herpiana; Pulungan, Dhia Nurmiyah; Anggun, Anggun; Aminullah, Aminullah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze factually about the implementation of the foundation of curriculum development in the 2013 curriculum with the independent curriculum. This research analysis is presented with descriptive qualitative method with literature review. This study examines literature in the form of books and scientific articles sourced from Google Scholer, ResearchGate and various journals that have national-based data. The data generated can produce valid results by looking at one study with other studies. In addition, the literature review can be used as a method to see and map the basis of curriculum development in the 2013 curriculum and that of the independent curriculum. Based on the results of the research conducted, it was found that the 2013 curriculum uses a foundation of curriculum development based on philosophical, legal, theoretical, empirical and conceptual values. Meanwhile, in the independent curriculum, the foundation of curriculum development that is implemented is the philosophical, psychological, sociological, scientific and technological and historical foundations. With a solid foundation, the resulting curriculum will be strong, that is, the educational programme can produce educated people in accordance with the nature of humanity, both for present life and for welcoming future life